2014
DOI: 10.1115/1.4027731
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered Stromal Cell-Derived Factor-1α Analogue Delivered as an Angiogenic Therapy Significantly Restores Viscoelastic Material Properties of Infarcted Cardiac Muscle

Abstract: Ischemic heart disease is a major health problem worldwide, and current therapies fail to address microrevascularization. Previously, our group demonstrated that the sustained release of novel engineered stromal cell-derived factor 1-a analogue (ESA) limits infarct spreading, collagen deposition, improves cardiac function by promoting angiogenesis in the region surrounding the infarct, and restores the tensile properties of infarcted myocardium. In this study, using a well-established rat model of ischemic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…None of these strategies fully eliminate the infarct scar, however, and thus the difficult balance between LV compliance and stiffness remains a potential pitfall. Indeed, our team has previously investigated the impact of various exogenous myocardial repair-based therapies on LV biomechanics after MI, including tissue-engineered constructs 31,32 , and angiogenic cytokines [33][34][35][36] , observing variable degrees of biomechanical recovery but often not a full normalization of mechanical properties. www.nature.com/scientificreports www.nature.com/scientificreports/ Consistent with previous studies of natural heart regeneration using a neonatal mouse MI model [15][16][17] , we observed that P1 mice develop minimal collagen scar by 4 weeks following MI, while P7 mice exhibit significant replacement of cardiac muscle with collagen scar.…”
Section: Discussionmentioning
confidence: 99%
“…None of these strategies fully eliminate the infarct scar, however, and thus the difficult balance between LV compliance and stiffness remains a potential pitfall. Indeed, our team has previously investigated the impact of various exogenous myocardial repair-based therapies on LV biomechanics after MI, including tissue-engineered constructs 31,32 , and angiogenic cytokines [33][34][35][36] , observing variable degrees of biomechanical recovery but often not a full normalization of mechanical properties. www.nature.com/scientificreports www.nature.com/scientificreports/ Consistent with previous studies of natural heart regeneration using a neonatal mouse MI model [15][16][17] , we observed that P1 mice develop minimal collagen scar by 4 weeks following MI, while P7 mice exhibit significant replacement of cardiac muscle with collagen scar.…”
Section: Discussionmentioning
confidence: 99%
“…SDF-1α administration after MI appears to increase the elasticity of the border zone and strengthens the fibrotic myocardium, which may provide a mechanical advantage to CMs and attenuate adverse remodeling ( Hiesinger et al, 2012 ). In addition to naturally occurring small molecules such as SDF-1α, engineered analogs such as ESA have demonstrated the ability to preserve biaxial mechanical properties of the native myocardium, improve myocardial relaxation, reduce infarct size, reduce ventricular thinning, and improve ventricular function ( MacArthur et al, 2013b ; Trubelja et al, 2014 ; Wang et al, 2019a ).…”
Section: Biomechanical Engineeringmentioning
confidence: 99%
“…In addition to naturally occurring small molecules such as SDF-1α, engineered analogs such as ESA have demonstrated the ability to preserve biaxial mechanical properties of the native myocardium, improve myocardial relaxation, reduce infarct size, reduce ventricular thinning, and improve ventricular function (MacArthur et al, 2013b;Trubelja et al, 2014;Wang et al, 2019a). While biomechanical approaches to emulate the properties of native myocardium have shown promise and should continue to be investigated, naturally regenerated myocardium in a neonatal mouse MI model successfully replicates the mechanical properties of native uninjured myocardium (Wang et al, 2020a).…”
Section: Biomechanical Engineeringmentioning
confidence: 99%
“…This will be overcome by introducing a biaxial testing method. 13,31 An additional limitation is that this test was not conducted in different directions. Multidirectional myocardial properties could be obtained with the information of myocardial alignment.…”
mentioning
confidence: 99%